2019
DOI: 10.2174/1874285801913010001
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of a Full-scale UASB Reactor Treating Brewery Wastewater Using Illumina MiSeq Sequencing

Abstract: Background:The efficiency of biological wastewater treatment plant is determined by bacterial metabolism. There are data on the effect of operational parameters on microbial consortia present in laboratory scale reactor. However, knowledge on the full-scale reactor is still limited at present, hence the need to define the relations between the microbial structure and the performance of full-scale reactor. Objective:In this study, the microbial community structure in a full-scale UASB reactor treating brewery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The presence of Betaproteobacteria class members, such as Desulfobacteraceae and Desulfobulbacteraceae, was observed in all three units, with similar abundance (Figures 7a and 8a). Members of the phylum Proteobacteria, such as Betaproteobacteria and Deltaproteobacteria, have been reported to participate in the sulfur cycle in CW [22] and anaerobic digestion processes [68,89]. In addition, Meyer et al [68] found that the presence of sulfur, potassium, manganese, total nitrogen, and total phosphorus in the wastewater contributed to variation in the structure and composition of families related to the sulfur cycle.…”
Section: Families Degrading Organic Mattermentioning
confidence: 99%
“…The presence of Betaproteobacteria class members, such as Desulfobacteraceae and Desulfobulbacteraceae, was observed in all three units, with similar abundance (Figures 7a and 8a). Members of the phylum Proteobacteria, such as Betaproteobacteria and Deltaproteobacteria, have been reported to participate in the sulfur cycle in CW [22] and anaerobic digestion processes [68,89]. In addition, Meyer et al [68] found that the presence of sulfur, potassium, manganese, total nitrogen, and total phosphorus in the wastewater contributed to variation in the structure and composition of families related to the sulfur cycle.…”
Section: Families Degrading Organic Mattermentioning
confidence: 99%
“…Figure 7 depicts the granular structure of thermophilic and mesophilic methanogens via scanning electronic microscopy (SEM), which is suitable to determine the morphology of the microbial species in anaerobic digestion [52]. For each sample, the images are presented with 15,000× magnification that permits visualization of different types of sludge developed in the reactors and detailed morphological features of the microbial species.…”
Section: Scanning Electronic Microscopymentioning
confidence: 99%